Minimum Edge Cuts in Overlay Networks - Schweichhart, Jonas

Unifying Gathering Protocols for Swarms of Mobile Robots - Castenow, Jannik; Harbig, Jonas; Meyer auf der Heide, Friedhelm (Lecture Notes in Computer Science)

Polymere unter Dehnung: Untersuchung der Filamententstehung von Polymerblends und deren Instabilitätsentstehung durch Partikeln - Temborius, Fiona; Neukötter, Moritz

Compact Metasurface-Based Optical Pulse-Shaping Device - Geromel, René; Georgi, Philip; Protte, Maximilian; Lei, Shiwei; Bartley, Tim; Huang, Lingling; Zentgraf, Thomas (Nano Letters)
Dispersion is present in every optical setup and is often an undesired effect, especially in nonlinear-optical experiments where ultrashort laser pulses are needed. Typically, bulky pulse compressors consisting of gratings or prisms are used to address this issue by precompensating the dispersion of the optical components. However, these devices are only able to compensate for a part of the dispersion (second-order dispersion). Here, we present a compact pulse-shaping device that uses plasmonic metasurfaces to apply an arbitrarily designed spectral phase delay allowing for a full dispersion control. Furthermore, with specific phase encodings, this device can be used to temporally reshape the incident laser pulses into more complex pulse forms such as a double pulse. We verify the performance of our device by using an SHG-FROG measurement setup together with a retrieval algorithm to extract the dispersion that our device applies to an incident laser pulse.
Keywords: Mechanical Engineering; Condensed Matter Physics; General Materials Science; General Chemistry; Bioengineering

Hard carbon microspheres with bimodal size distribution and hierarchical porosity via hydrothermal carbonization of trehalose - Wortmann, Martin; Keil, Waldemar; Diestelhorst, Elise; Westphal, Michael; Haverkamp, René; Brockhagen, Bennet; Biedinger, Jan; Bondzio, Laila; Weinberger, Christian; Baier, Dominik; Tiemann, Michael; Hütten, Andreas; et al. (RSC Advances)
Hydrothermal carbonization (HTC) is an efficient thermochemical method for the conversion of organic feedstock to carbonaceous solids. HTC of different saccharides is known to produce microspheres (MS) with mostly Gaussian size distribution, which are utilized as functional materials in various applications, both as pristine MS and as a precursor for hard carbon MS. Although the average size of the MS can be influenced by adjusting the process parameters, there is no reliable mechanism to affect their size distribution. Our results demonstrate that HTC of trehalose, in contrast to other saccharides, results in a distinctly bimodal sphere diameter distribution consisting of small spheres with diameters of (2.1 ± 0.2) μm and of large spheres with diameters of (10.4 ± 2.6) μm. Remarkably, after pyrolytic post-carbonization at 1000 °C the MS develop a multimodal pore size distribution with abundant macropores > 100 nm, mesopores > 10 nm and micropores < 2 nm, which were examined by small-angle X-ray scattering and visualized by charge-compensated helium ion microscopy. The bimodal size distribution and hierarchical porosity provide an extraordinary set of properties and potential variables for the tailored synthesis of hierarchical porous carbons, making trehalose-derived hard carbon MS a highly promising material for applications in catalysis, filtration, and energy storage devices.
Keywords: General Chemical Engineering; General Chemistry

Theoretische Beschreibung des Polymerverhaltens in Polymerlösungen und - schmelzen: Simulationen anhand des Rolie-Poly-Modells - Bünder, Dirk; Neukötter, Moritz

Digital occupants – Wie digitale Medien die kommunikative Aushandlung von Freundschaften verändern - Teichert, Jeannine

Mediale Identitätsaushandlungen deutscher MigrantInnen im Zuge des Brexit - Teichert, Jeannine; Meister, Dorothee M. (MedienPädagogik)

"Lesungen vor Kindern sind für mich Theater" / Salah Naouras Sicht auf Wirkliches und Mögliches in Autor*innenlesungen für Kinder in der Schule - Kruse, Iris; Maubach, Bernd; Tönsing, Johanna (Salah Naoura)

Held*innenträume. Superheldinnen und Superhelden selbst erdacht / Paderborner Grundschulkinder werden auf die Begegnung mit Salah Naoura vorbereitet - Kruse, Iris; Schäfer, Luisa Maria (Salah Naoura)

Salah Naoura

Algorithms for the genome median under a restricted measure of rearrangement - Silva, Helmuth O.M.; Rubert, Diego P.; Araujo, Eloi; Steffen, Eckhard; Doerr, Daniel; Martinez, Fábio V. (RAIRO - Operations Research)
Ancestral reconstruction is a classic task in comparative genomics. Here, we study the genome median problem, a related computational problem which, given a set of three or more genomes, asks to find a new genome that minimizes the sum of pairwise distances between it and the given genomes. The distance stands for the amount of evolution observed at the genome level, for which we determine the minimum number of rearrangement operations necessary to transform one genome into the other. For almost all rearrangement operations the median problem is NP-hard, with the exception of the breakpoint median that can be constructed efficiently for multichromosomal circular and mixed genomes. In this work, we study the median problem under a restricted rearrangement measure called c4-distance, which is closely related to the breakpoint and the DCJ distance. We identify tight bounds and decomposers of the c4-median and develop algorithms for its construction, one exact ILP-based and three combinatorial heuristics. Subsequently, we perform experiments on simulated data sets. Our results suggest that the c4-distance is useful for the study the genome median problem, from theoretical and practical perspectives.
Keywords: Management Science and Operations Research; Computer Science Applications; Theoretical Computer Science

Sets of r-graphs that color all r-graphs - Ma, Yulai; Mattiolo, Davide; Steffen, Eckhard; Wolf, Isaak Hieronymus (arXiv:2305.08619)

Thermo‐chemo‐mechanical modelling of a curing process combined with mean‐field homogenization methods at large strains - Lenz, Peter; Mahnken, Rolf (PAMM)
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics

Model-driven Collaborative Design of Professional Education Programmes With Extended Online Whiteboards - Wolters, Dennis; Engels, Gregor (MODELSWARD'23)

A Non-Linear Mean-Field Debonding Model at Large Strains for the Analysis of Fibre Kinking in Ud Composites - Cheng, Chun; Song, Chunlei; Mahnken, Rolf; Yuan, Zhipeng; Yu, Liang; Ju, Xiaozhe

A thermodynamic framework for the phase‐field approach considering carbide precipitation during phase transformations - Westermann, Hendrik; Mahnken, Rolf (PAMM)
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics

A finite strain gradient theory for viscoplasticity by means of micromorphic regularization - Hamdoun, Ayoub; Mahnken, Rolf (PAMM)
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics

Ratings Meet Prices: The Dynamic Relationship of Quality Signals - Kaimann, Daniel; Spiess Bru, Clarissa Laura Maria; Frick, Bernd (Journal of Wine Economics)

Ultrafast Proton Transfer Pathways Mediated by Amphoteric Imidazole - Codescu, M.-A.; Kunze, T.; Weiß, M.; Brehm, Martin; Kornilov, O.; Sebastiani, D.; Nibbering, E. T. J. (J. Phys. Chem. Lett.)